A penhora na execução fiscal: penhora on line e o princípio da menor onerosidade - Rosa, Íris Vânia Santos (2013)
This PHD Thesis has simple goals. Based in reality brought by our courts, we intend to treat about the tax foreclosure process governed by Law No. 6.830/1980 and expropriation measure known as Garnishment "On Line" within the context of the principle of least burden to the debtor. Initially highlight the reality, linked to knowledge, working with Comparative Language Social and Legal Language in the context of the structure of our legal system, determining a form of communication between humans - language itself. That justified our approach to semiotics understood as the General Theory of Signs - split plan syntactic, semantic and pragmatic. Is it true that in general terms and abstract born the tax obligation, which formalized its essential element is the tax credit. Moreover, with the tax legal fact, hypothesis poured language competent to give tax incidence. We seek an approach to valuing the law, especially constitutional principles guiding the organs judges and legal standards as a paradigm homelands, in the context of a rule complete. These considerations, it is possible to identify the timing of Tax Enforcement in the process of positive law in one moves from the point of abstraction higher expressions of the law to those of greater concreteness externadas, for example, the attachment of assets to guarantee certain outstanding debt. Finally, despite various forms of Garnishment accepted in our legal system, as the Bank Guarantee, the Real Estate, the novelty of the surety, and also the decisions of the courts in relation to these guarantees, we will give special attention to Attachment " On Line "and its main features, so we can demonstrate the effectiveness of this measure and its usefulness in completing the Executive Committee, considering the principle of least burden to the debtor